Advancement of the culture of written expression in pupils - Đorđev, Ivana Đ (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2015)
Starting from the research which suggests that scientific concepts in the area of scientific knowledge relating to teaching process are underdeveloped, this paper presents three methodical applications intended for the secondary school instruction in orthography. Their design requires (conceptual) thinking from pupils which form the basis of the very concept of test for the assessment of acquisition of (scientific) concepts. They are: Test of Associations (Test A), Test of Tables of Concept Attributes (Test C) and Test of Definitions (Test D). Here we aimed at the advancement of the teaching of orthography and culture of written expression in secondary school pupils. The applications offered can be modified and implemented during various phases of the class (in their entirety or in part), in both regular and advanced teaching, as well as in remedial classes if appropriately simplified.